Mathematical and Experimental Investigation on Advanced PLL for Cascaded H-Bridge Multilevel Inverter in Active Filtering Application. Issue 3 (7th February 2019) - Ray, Soumyadeep; Gupta, Nitin; Avtar Gupta, Ram
Abstract: Cascaded H-bridge multilevel inverter (CHB-MLI)-based shunt active power filter (SAPF) is one of the finest solutions for power quality improvement in case of medium-voltage distribution sector. Performance of SAPF degrades due to the presence of DC offset and harmonics in the grid voltage since this will result phase angle and frequency error. Therefore, modified single-phase synchronous reference frame theory comprising of advanced PLL is presented in this article. The advanced PLL can track frequency and phase angle accurately even though source voltage is having DCor harmonic content. A detailed mathematical modeling and stability analysis of this PLL is presented using Routh-Hurwitz criteria. A novel systematic design procedure using gravitational search algorithm (GSA) and an Eigen value analysis is proposed for calculating optimal PLL parameters. Closed-loop SAPF control stability is tested using root-locus analysis. An extensive experimental analysis of the proposed control applied to CHB-MLI-based SAPF has been performed under distorted source voltage and non-linear loading conditions to show the effectiveness of the proposed control over recently published work. Source current maintains its sinusoidal shape, properly synchronized with grid voltage and having distortion limit in compliance with IEEE-519 standard irrespective of source voltage conditions during the operation of SAPF.